The succession of rhizosphere microbial community in the continuous cropping soil of tobacco - Li, Guitong; Gong, Pengfei; Zhou, Jie; Wang, Lin; Song, Xin; Ding, Penghui; Jin, Yunfeng; Zhang, Yuzhen; Zhou, Xiaoqian; Yang, Jianming; Wang, Zhaobao; Yun, Long; et al. (Frontiers in Environmental Science, 2024)
Flue-cured tobacco is an important economic crop that is not tolerant of continuous cropping, which could raise some influences on its planting soil conditions including rhizosphere microbial communities and soil physicochemical properties. However, the relationship between the two aspects under continuous cropping conditions is still lacking a clear understanding. This study investigated the succession of rhizosphere microbial community in continuous tobacco cropping soil for 1 year, 3 years, 5 years, 8 years, 10 years, 15 years, and 30 years. The results suggested that continuous cropping could significantly enrich soil available nitrogen, available phosphorus, available potassium, and organic matter. Meanwhile, the alpha diversity of bacterial community has significantly reduced along with continuous cropping, indicating significant changes in the structure of bacterial and fungal communities. Based on linear discriminant analysis effect size (LEfSe), 173 bacterial and 75 fungal genera were identified with significant differences, respectively. The bacterial genera, Sphingomonas, Streptomyces and Microvirga, were significantly positively correlated with continuous cropping years. The fungal genera, Tausonia, Solicocozyma, Pseudomycohila, and Fusarium, also showed significantly positively correlation with continuous cropping years. While, the fungal genera, Olpidium, Cephaliophora, and Cercophora, presented an opposite correlation. Meanwhile, these genera presented significant associations with different soil physicochemical properties. In summary, this work would provide reference for soil management and scientific fertilization of tobacco under continuous cropping conditions.